Integrating Culturally Responsive Teaching and Audio-Visual Tools to Boost Vocabulary Skills of Students Junior High School of Dharma Wanita Medan: Penelitian - Muliawan Prayuda Putra; Yulia Sari Harahap; Ahmad Laut Hasibuan; Nazriani Lubis (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the effect of a Culturally Responsive Teaching (CRT) approach integrated with audio-visual media on students' vocabulary mastery at SMP Dharma Wanita Medan. A quasi-experimental method was employed involving 80 eighth-grade students divided into control and experimental groups. The experimental group received instruction through CRT-based audio-visual materials, while the control group was taught using conventional methods. Data were collected using pre-tests and post-tests and analyzed with an independent sample t-test. The findings showed a statistically significant improvement in vocabulary scores in the experimental group (Sig. 2-tailed = 0.004), highlighting that culturally relevant media can significantly enhance vocabulary acquisition, motivation, and student engagement. This demonstrates that the integration of CRT with audio-visual media is effective in promoting student engagement, contextual learning, and vocabulary retention in EFL settings. The study recommends that educators adopt CRT principles and utilize localized audiovisual content to foster inclusive and meaningful language learning experiences.